Optical Coherence Tomography Angiography of Two Choroidal Nevi Variants - Victor M. Villegas; Armando L. Monroig; Lazaro H. Aguero; Stephen G. Schwartz (Case Reports in Ophthalmological Medicine)
Optical coherence tomography angiography (OCT-A) is a recently established noninvasive technology for evaluation of the retinal and choroidal vasculature. The literature regarding the findings in choroidal nevi is scarce. We report the OCT-A findings associated with two different variants. Subject one had decreased vascular flow signal in the choroidal, choriocapillaris, deep retinal, and superficial retinal layers. Subject two had decreased vascular flow signal in the choroidal, choriocapillaris, and deep retinal layers with a normal vascular flow signal in the superficial retinal layer. To our knowledge, these patterns of decreased vascular flow signals have not been previously reported using OCT-A. This may be due to blockage from the choroidal nevus, true diminished blood flow (ischemia), or other factors.